2016
DOI: 10.1186/s12886-016-0258-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and ocular biometric parameters changes in migraine

Abstract: BackgroundThe aim of this study was to assess the intraocular pressure and ocular biometric parameters in migraine patients during acute migraine attacks and compare them with painless period and healthy controls using a new optical biometer AL-Scan.MethodsIn this prospective, case–control study, the axial length, corneal curvature radius, anterior chamber depth, central corneal thickness, and pupil size of 40 migraine patients during acute migraine attacks and painless period and 40 age- and sex-matched healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…A further 1472 papers were also excluded following title and abstract review. Of the remaining 25 publications retained for further assessment and a full-text review, nine papers were excluded for the following reasons: review (n = 1) [ 18 ] ; no focus on the relationship between the migraine and POAG (n = 3) [ 19 21 ] ; comparison of the incidence of migraine between familial and sporadic glaucoma (n = 1) [ 22 ] ; no provision of RRs or ORs or data for their calculation (n = 3) [ 23 25 ] ; letter (n = 1) [ 26 ] ; not case–control or cohort design (n = 5). [ 27 – 31 ] Ultimately, 11 studies, [ 9 , 10 , 32 40 ] including 3 cohort or nested case–control, [ 10 , 32 , 35 ] and 8 case–control studies, [ 9 , 33 , 34 , 36 40 ] were included in the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A further 1472 papers were also excluded following title and abstract review. Of the remaining 25 publications retained for further assessment and a full-text review, nine papers were excluded for the following reasons: review (n = 1) [ 18 ] ; no focus on the relationship between the migraine and POAG (n = 3) [ 19 21 ] ; comparison of the incidence of migraine between familial and sporadic glaucoma (n = 1) [ 22 ] ; no provision of RRs or ORs or data for their calculation (n = 3) [ 23 25 ] ; letter (n = 1) [ 26 ] ; not case–control or cohort design (n = 5). [ 27 – 31 ] Ultimately, 11 studies, [ 9 , 10 , 32 40 ] including 3 cohort or nested case–control, [ 10 , 32 , 35 ] and 8 case–control studies, [ 9 , 33 , 34 , 36 40 ] were included in the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…There was not a statistically significant difference in intraocular pressure between the migraine patients during acute migraine attacks, painless period, and the controls. Also, the ocular biometric parameters did not significantly vary during the acute migraine attacks 18 . In this study, we aimed to compare anterior chamber depth (ACD), vitreous chamber depth (VCD), lens thickness (LT), axial length (AL), central corneal thickness (CCT), corneal volume (CV), anterior chamber volume (ACV), iridocorneal angle (ICA), pupil diameter (PD), intraocular pressure (IOP), mean keratometry (Km), and spherical equivalent measurements in children with migraine and healthy children and to investigate the relationship between PD and migraine with visual aura (photophobia).…”
Section: Introductionmentioning
confidence: 81%
“…In another study based on the vasogenic theory, there was no difference in ganglion cell layer (GCL) thickness compared to the control group, whereas differences were detected in some RNFL quadrants and some optical disc parameters such as disc area and cup volume 17 . Although a study evaluating IOP change and ocular biometric parameters in adult migraine patients has been conducted previously 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have explored visual acuity and visual field testing in migraineurs, although they did not observe any differences between migraineurs and controls ( 13 , 14 ). Koban et al ( 15 ) studied intraocular pressure (IOP) and biometric parameters and found no relevant differences between migraineurs during the attack and the healthy controls.…”
Section: Introductionmentioning
confidence: 99%